The Dunayevskaya-Marcuse-Fromm correspondence, 1954-1978 : dialogues on Hegel, Marx, and critical theory - Anderson, Kevin, 1948-; Rockwell, Russell, 1952- (Studies in Marxism and humanism., 2012)
This volume contains the correspondence during the years 1954 to 1978 between Marxist-Humanist and feminist philosopher Raya Dunayevskaya (1910-87) and the Hegelian Marxist philosopher and social theorist Herbert Marcuse (1898-1979) and the psychologist and social critic Erich Fromm (1900-80). The exchanges show the deeply Marxist and humanist concerns of these theorists while also highlighting their significant differences on key issues in philosophy, politics, and psychology during the turbulent decades of the 1950s, 1960s, and 1970s.